The BOOMERANG MECHANISM IN HUMAN RIGHTS ADVOCACY: BALOCH LONG MARCH AGAINST CHINA-PAKISTAN ECONOMIC - Ameta Novelia Br Karo; Muhammad Indrawan Jatmika (Pena Wimaya, 2025)
Transnational advocacy networks (TANs) and the “boomerang” pattern of influence can bypass domestic repression and internationalise local human rights struggles, as shown by the 2023–2024 Baloch Long March. Pakistani activists led by the women's organisation Baloch Yakjehti Committee (BYC) marched from Gwadar to Islamabad to demand justice for enforced disappearances and extrajudicial killings in Balochistan, facing censorship, arbitrary arrests, and state violence. When local channels were blocked, movement leaders allied with international NGOs (Amnesty International, Human Rights Watch) and global media to present their plight to the UN and international public. This strategy led to UN expert statements in early 2025 and international media coverage, increasing pressure on Pakistan's government. This study examines how the Long March employed external pressure to highlight human rights violations associated with the China–Pakistan Economic Corridor, utilizing Keck and Sikkink's “boomerang” framework and other norm-based theories. Despite Pakistani authorities' repressive measures (information blackouts, protest bans), the international outcry raised the cost of rights abuses and internationalised the Baloch cause. This paper demonstrates how marginalized activists utilized global media and networks to advocate for domestic rights.